Clinical findings in congenital infection by Zika virus: a retrospective study in a reference hospital in Central-West Brazil - Cláudia de Paula Guimarães; Myrella Silveira Macedo; Maria Alves Barbosa; Solomar Martins Marques; Paulo Sucasas Costa; Ênio Chaves de Oliveira (BMC, 2019)
Background An increased number of congenital Zika virus infections with neurological and musculoskeletal malformations have been diagnosed worldwide, however, there are still several gaps in the knowledge about this infection, its associated mechanism, timing of transmission, and description of throughout findings of signs and symptoms, which is described in this paper. The purpose of this study is to describe aspects of congenital Zika syndrome (CZS) beyond the central nervous system comprising detailed delineation of all the other clinical findings. Methods A retrospective research developed using electronic medical records. We analyzed the files of 69 children with an initial diagnosis of microcephaly by Zika vírus who were born in 2015, 2016 and 2017, treated during the period from 2016 to 2017. Results The newborns presented several neurological and musculoskeletal malformations, eye damage, hearing impairment and other malformations. Conclusions The present study has significant impact for health care teams following lactents with Congenital Zika Syndrome.